MANIFESTASI ECO-ECONOMY NILAI PERUSAHAAN: KONTRIBUSI PROFITABILITAS, GROWTH OPPORTUNITY, MEDIA EXPOSURE, DAN KINERJA LINGKUNGAN (Proceedings Law, Accounting, Business, Economics and Language, 2025)
This study aims to analyze the influence of profitability, growth opportunity, media exposure, and environmental performance on firm value, considering the dynamics of the Indonesian capital market and the growing attention to sustainability aspects. The analysis was conducted using a quantitative approach with secondary data from industrial sector companies listed on the Indonesia Stock Exchange. The results indicate that profitability significantly affects firm value, while growth opportunity, media exposure, and environmental performance have no significant effect. The findings suggest that investors still tend to focus on financial indicators when making investment decisions. Nevertheless, non-financial aspects such as environmental management and media communication remain strategically important in supporting the company’s long-term reputation. Therefore, companies are encouraged to improve profitability while also enhancing information transparency and environmental performance as a form of commitment to sustainable business practices.